Understanding critical concepts in engaged research to promote health resilience: the case of a systems analysis and epistemically just rural health development project in South Africa - Duxbury, Theodore Orlando (Rhodes University, Faculty of Pharmacy, Pharmacy)
Access restricted. Expected release date 2025.
Keywords: Uncatalogued